Izzivi digitalne preobrazbe (University of Maribor Press, 2022)
Challenges of Digital Transformation. Slovenia, the European Union, and almost the whole world are rapidly moving towards a digital transformation into a digital future, sparking numerous debates in all areas of social and economic life. The expert monograph Challenges of Digital Transformation addresses the issues Slovenian companies face when introducing and applying digitalisation in their business and production processes. The chapters are authored by students from the University of Maribor, who researched the challenges that selected Slovenian companies and non-economic organisations face in digital transformation. Their solutions will help other companies, researchers, students and anyone facing similar problems. The chapters are primarily case-based and interdisciplinary, with students from six different faculties, which adds value to the monograph.